2018
DOI: 10.7196/samj.2018.v108i11.13252
|View full text |Cite
|
Sign up to set email alerts
|

Lost to follow-up: Challenges to conducting orthopaedic research in South Africa

Abstract: Kimberley Provincial Hospital provides the sole public sector orthopaedic surgical service to the entire Northern Cape Province of South Africa (SA). Ankle fractures form part of the trauma burden and pose a challenge owing to high numbers and limited resources. The incidence of ankle fracture is reported to be 169.7/100 000/year. [1] Currently there are no statistics on the incidence in the Northern Cape. An alternative surgical method of treatment was explored in the form of a prospective cohort series, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
3
12
1
Order By: Relevance
“…The factor of distance can be linked to the finding in this research of 'lack of money for transport' arising as a reason for dropout. The distances in the present research were far less than those reported by Badenhorst et al 38 thus it is likely that poor transport infrastructure and poverty, rather than purely distance, are reasons for the high dropout rates. Affordability as a dimension of accessibility 12 is reflected here, with the constrained economic capacity of the population.…”
Section: Retentioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The factor of distance can be linked to the finding in this research of 'lack of money for transport' arising as a reason for dropout. The distances in the present research were far less than those reported by Badenhorst et al 38 thus it is likely that poor transport infrastructure and poverty, rather than purely distance, are reasons for the high dropout rates. Affordability as a dimension of accessibility 12 is reflected here, with the constrained economic capacity of the population.…”
Section: Retentioncontrasting
confidence: 69%
“…Factors influencing the follow-up of patients, however is intractably linked to their setting. In a South African Orthopaedic study, Badenhorst et al 38 identified three main factors influencing loss to follow-up, namely distance to travel, BMI and HIV status. The factor of distance can be linked to the finding in this research of 'lack of money for transport' arising as a reason for dropout.…”
Section: Retentionmentioning
confidence: 99%
“…Previous studies investigating hospitalbased follow-up in orthopaedics have for the most part focused on trauma follow-up in a developed country setting, including wellresourced clinical trials. [29][30][31][32][33][34] Although Dunn et al [15] alluded to poor compliance with tertiary hospital follow-up among spinal TB patients in the Western Cape, this concern fell beyond the main objective of the present study and was not subsequently investigated.…”
Section: Researchmentioning
confidence: 83%
“…The time period for the dataset was 1 January 2012 -31 December 2017. Finally, distance from the RESEARCH hospital was taken as the shortest distance by road between the patient's area of residence and the hospital according to Google Maps [30,34] and reported as both a continuous variable and a categorical variable, < or ≥50 km. All study data were captured by a single investigator using custom-designed electronic data capture forms in order to optimise data quality and consistency.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation